Canon, Repetition, and the Opponent: Interpretation in the History of Ideas. Issue 1 (17th February 2020) - Levene, Nancy
Abstract: This essay considers two concepts of repetition in thinking about canon, the history of ideas, and the work of an opponent, both real and fantastical. I take up these motifs in a variety of figures and cases, but principally in Søren Kierkegaard's reading of the biblical Abraham in Fear and Trembling, a text rich in interpretive challenges. How might readers in the humanities contend with interpretive rivals while investing in the power of diverse readings? The argument turns on the relationship between the struggle for self‐consciousness, understood through Hegel and Freud as an appointment with otherness, and the work of interpretation, understood as the endeavor to understand others, including other texts, other minds, and one's own mind. What is the aim of interpretation? How does interpretation fail? To which history of ideas is a reader responsible?